Optimizing the Transition Program for Students with Special Needs in Vocational High Schools - Muhammad Saifour Farochi (Universitas Negeri Makassar, 2022)
The implementation of inclusive education that has been running in Indonesia should be able to explore and improve the abilities of students with special needs (PDBK), in order to become human beings who have character, are capable, creative and independent. However, many PDBK who have graduated from formal education are still experiencing problems of independence and life skills so they still depend on their families for their lives. This study aims to explore the optimization of the transition program for PDBK in SMK Negeri 1 Buduran starting from the planning, organizing, implementing and monitoring processes. The transition program is a program designed based on the results of an analysis of the needs, barriers, talents, interests and expectations of the GDPK to prepare as optimally as possible by involving the most comprehensive changes that PDBK may face in order to lead a better post-school life. The research design used a qualitative approach with a descriptive method. Data were collected by interview, observation and documentation techniques. Meanwhile, when the research was carried out until the data were collected completely and in depth, starting from the preparation to reporting the research results. The results of the study show the success of optimizing the transition program, as seen from the large number of PDBK absorbed in the world of work, and entrepreneurship based on tracking data for 2017-2020 graduates who have successfully passed 30 PDBK with the result that 11 children/36.6% have worked, 6 children/ 20% are entrepreneurs, 9 children/30% children continue to college and the remaining 4 children/13.3% are looking for work. Constraints faced are limited budgets, lack of support from the industrial world (DUDI) in the field practice process and labor recruitment. The solutions implemented by schools include conducting internal studies on the transition program, inviting the active role of committees, parents and seeking to continue to promote the achievements and potential of PDBK.